Efforts to increase protein in Tempe can provide positive values for native Indonesian food. The amount of remaining egg white in the bread industry can be used in making soybean Tempe. Egg white which is rich in albumin has never been used in the manufac - Novitasari Priskalia Puter; Lusiawati Dewi; Anggara Mahardika (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2020)
Efforts to increase protein in Tempe can provide positive values for native Indonesian food. The amount of remaining egg white in the bread industry can be used in making soybean Tempe. Egg white which is rich in albumin has never been used in the manufacture of soybean tempeh by the producer. This research aims to determine the effect of adding raw and steamed egg whites on the protein content of soybean Tempe. This study used a Completely Randomized Design (CRD) with 3 replications. The concentrations of egg whites used in the research included 0%, 2%, 4%, 6%, 8%, and 10%. The research instrument used was the observation sheet for protein content using the Lowry method. The research data were dissolved protein content. The data analysis technique used Two Way ANOVA. The results of the research showed that there was no effect of adding raw and steamed egg whites on soybean Tempe protein content (P >0.05). However, the addition of raw egg whites can increase the protein content of soybean Tempe, compared to steamed egg whites. The conclusion of this research is the addition of raw and steamed egg whites does not have a significant effect on the protein content of soybean Tempe. The right type of egg white flour to increase the protein content of soybean Tempe is raw egg white flour with a protein content of 15.0 per 100 grams